2013
DOI: 10.1128/jcm.00097-13
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Reactivation of Human Herpesvirus 6 in Generalized Lymphadenopathy in a Patient with Drug-Induced Hypersensitivity Syndrome

Abstract: The present case provides direct evidence of human herpesvirus 6 reactivation in resected lymph node tissue in a patient with drug-induced hypersensitivity syndrome. This case clearly demonstrates that appropriate pathological evaluation of lymphadenopathy for drug-induced hypersensitivity syndrome, which mimics malignant lymphoma in clinical, radiological, and pathological findings, is required. CASE REPORTA 57-year-old woman was referred to our department because of generalized erythema involving mainly her … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 13 publications
2
15
0
Order By: Relevance
“…Many members of the Hepeviridae family have been reported to be reactivated in DIHS patients. A few reports demonstrated these latent viruses pathologically: HHV-6 in monocytes of skin lesions (2), atypical Reed-Sternberg-like cells of lymph nodes (20), and Treg cells of lymph nodes (21); and CMV in skin lesions (22). The present case showed inclusion bodies and multinucleated giant cells in the lung specimens, which suggest that the causal virus might have been a member of the Herpesviridae family, which are commonly found in latent infections in humans.…”
Section: Discussionmentioning
confidence: 99%
“…Many members of the Hepeviridae family have been reported to be reactivated in DIHS patients. A few reports demonstrated these latent viruses pathologically: HHV-6 in monocytes of skin lesions (2), atypical Reed-Sternberg-like cells of lymph nodes (20), and Treg cells of lymph nodes (21); and CMV in skin lesions (22). The present case showed inclusion bodies and multinucleated giant cells in the lung specimens, which suggest that the causal virus might have been a member of the Herpesviridae family, which are commonly found in latent infections in humans.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that herpes virus reactivation, most notably HHV-6, was the common underlying factor for the multiple drug reactions [38][39][40][41][42], although that was not proven in our case. We conclude that the HLA-B*58 haplotype may be a risk factor for drug hypersensitivity syndrome with imatinib therapy in patients who react to allopurinol, but this needs to be confirmed in further studies.…”
Section: Discussionmentioning
confidence: 67%
“…Although lymphadenopathy is very common among the patients with DRESS syndrome, so far there have been a few immunohistochemical studies of the lymphadenopathy [13,14]. A previous study demonstrated the presence of HHV-6-infected cells in the lymph node in a case of DRESS syndrome [14].…”
Section: Discussionmentioning
confidence: 97%
“…A few cases of HHV-6-associated acute lymphadenitis have been reported in pathological studies, including one in a patient with DRESS syndrome [13,14]. The expression of CD25 and FoxP3 is known to be induced by infections with viruses including the human T-lymphotropic virus 1 [15], and HHV-6 [16,17], but there have been no reports so far describing HHV-6 activation in Tregs or CD25(+)/FoxP3(+) cells.…”
Section: Other Similar and Contrasting Cases In The Literaturementioning
confidence: 95%